Studi Komparatif Dua Model Skema Sistem Smart Charging Eksternal untuk Laptop - Ahmad Afief Amrullah; Arief Setyanto; Sudarmawan Sudarmawan (Universitas PGRI Yogyakarta, 2020)
In recent years, external smart charging, especially on laptop devices, has become quite an interesting topic due to the need for a response to a decrease in battery capacity and damage. As the development of embedded systems such as Arduino which is commonly used, this system offers more flexible data communication, which initially used cables to be wireless, ranging from Bluetooth to WiFi. As for this topic, there are controls based on the user's electricity needs and the condition of the electrical system, which is called dynamic demand control. The key to this method is the frequency of the electricity network and the battery. This method can provide extensions to smart charging to only charge when needed. The positive impact of using this method in addition to preventing the battery from being damaged is electricity savings. In this study the authors tried to study two models of the smart charging system schemes that have never been compared, namely the standalone and centralized models. The results of this study indicate that although the centralized model is more efficient in terms of reading the frequency value of the electricity network, in terms of performance the standalone model is more stable and reliable.